Cluster analysis for the identification of clinical phenotypes among antiphospholipid antibody-positive patients from the APS ACTION Registry. (October 2020) - Zuily, Stéphane; Clerc-Urmès, Isabelle; Bauman, Cédric; Andrade, Danieli; Sciascia, Savino; Pengo, Vittorio; Tektonidou, Maria G; Ugarte, Amaia; Gerosa, Maria; Michael Belmont, H; Zamorano, Maria Angeles Aguirre; Fortin, Paul; et al.
Objective: This study aimed to use cluster analysis (CA) to identify different clinical phenotypes among antiphospholipid antibodies (aPL)-positive patients. Methods: The Alliance for Clinical Trials and International Networking (APS ACTION) Registry includes persistently positive aPL of any isotype based on the Sydney antiphospholipid syndrome (APS) classification criteria. We performed CA on the baseline characteristics collected retrospectively at the time of the registry entry of the first 500 patients included in the registry. A total of 30 clinical data points were included in the primary CA to cover the broad spectrum of aPL-positive patients. Results: A total of 497 patients from international centres were analysed, resulting in three main exclusive clusters: (a) female patients with no other autoimmune diseases but with venous thromboembolism (VTE) and triple-aPL positivity; (b) female patients with systemic lupus erythematosus, VTE, aPL nephropathy, thrombocytopaenia, haemolytic anaemia and a positive lupus anticoagulant test; and (c) older men with arterial thrombosis, heart valve disease, livedo, skin ulcers, neurological manifestations and cardiovascular disease (CVD) risk factors. Conclusions: Based on our hierarchical cluster analysis, we identified different clinical phenotypes of aPL-positive patients discriminated by aPL profile, lupus or CVD risk factors. Our results, while supporting the heterogeneity of aPL-positive patients, also provide a foundation to understand disease mechanisms, create new approaches for APS classification and ultimately develop new management approaches.